Treatment of Corneal Perforation Using Periosteal Graft Technique With the Continuation of Penetrating Keratoplasty: Poster Presentation - Case Report - Resident - ADRIAN PRATAMA; Petty Purwanita; Anang Tribowo (Majalah Oftalmologi Indonesia, 2023)
Introduction : Corneal perforation occurs due to various conditions and management are based on the underlying cause. Modalities to treat corneal leaks is dependent on the size of corneal defect and include tissue adhesive, conjunctival flap, grafts and transplants. Penetrating Keratoplasty (PK) is effective to treat large corneal defect and to improve visual acuity (VA), but unfortunately PK is usually delayed due to availability. Case Illustration : A 17-years-old teenager was diagnosed with corneal perforation on his left eye, VA at initial visit was 1/300, positive seidel test, and shallow anterior chamber. Patient immediately underwent periosteal graft with subsequent PK surgery one month later. First until eight days postoperatively, VA improved from 3/60 to 6/30. Ten days after PK, a mechanical trauma caused the transplant to be detached, and VA greatly decreased to 1/300. Patient underwent immediate repair surgery. First day after surgery, VA was light perception. Eight days later, VA increased to 1/60 with concurrent iris prolapse. Iris repair was done immediately and eight days later VA increased to 6/60. At day sixteen, the final VA is 6/30. Discussion : Periosteal graft was performed to maintain ocular integrity. After waiting for a month, PK was performed to improve vision. This combination therapy was successful proven by VA improvement from 1/300 to 6/30. Conclusion : Periosteal graft is necessary to maintain ocular integrity while waiting for availability of donor cornea. Penetrating keratoplasty is an appropriate procedure for patients with large corneal leaks. It replaces all corneal structures, and it also improve visual function.